A Design New Panel Of Energy Roof House - Rahmad Rahmad (Sean Institute, 2022)
Energy from sunlight is collected and then converted into electrical energy. This energy can later be used to run various kinds of electronic devices, from turning on lights, moving motors, and many others. In this research using solar energy as an alternative energy to supply energy to portable fertilizer dryers in meeting household electricity needs and also helping farmers so they don't need electricity that is sucked up through the PLN.